Factors Influencing the Intentions to Adopt Technology of the Broiler Farmer in Livestock Region 3, Thailand - Wichean, Apisara; Sungsanit, Mullika (Trends in Sciences, 2022)
This research aimed to study the types and influence of mindsets, performance expectancy, effort expectancy, social influence and facilitating conditions on farmers’ intention to adopt a technology. The research participants were 110 broiler farmers in livestock region 3. The research used a questionnaire to collect quantitative data and analyse the data using frequency, percentage, mean, standard deviation, correlation coefficient and structural equation modeling with maximum likelihood estimation to analyse path coefficienct and structural relationships. The result showed that most of the participants have a growth mindset more than a fixed mindset. Performance expectancy, effort expectancy, social influence and facilitating conditions have directly affected boiler farmers’ intention to adopt the technology. Effort expectancy has a total effect on attitude toward using technology. Interestingly, facilitating conditions have shown the most considerable influence on attitude toward adopting the technology. Mindsets have an influence on effort expectancy and facilitating conditions. HIGHLIGHTS Most broiler farmers in livestock region 3 possess a growth mindset than a fixed mindset Performance expectancy, effort expectancy, social influence and facilitating conditions have direct effect on boiler farmers’ intention to adopt the technology Mindsets influence farmers’ perception of effort expectancy and facilitating conditions of adopting the technology